Prioritization of useful plant species to boost conservation and bioeconomy in Colombia: a case study in three biodiverse areas (2023)
A new big challenge for megadiverse countries is to develop in a sustainable way, while leveraging their economies and the conservation of ecosystems. Colombia is in search of nature-based solutions that help to improve local livelihoods and strengthen conservation projects, especially in biodiverse regions with historically complex socio-economic contexts. Creating Value Chain Networks (VCN) from sustainably harvested Non Timber Forest Products (NTFP), transformed into Natural Ingredients (NI) and final products, might contribute to buffer the transformation pressure of ecosystems in hotspots of deforestation. A community-based prioritization process was conducted in three biodiverse areas of Colombia to understand the NTFP and NI obtained from native useful plant species potential to boost Colombia’s bioeconomy. Through interdisciplinary methodologies that involved both social and natural sciences, 30 species with corresponding NTFP and NI were prioritized (10 for each pilot area). An extensive taxonomic and use diversity was found, from which the most representative families were Arecaceae, Fabaceae, Malvaceae, and Marantaceae, and the most important plant use category reported was food. When data was complemented with local surveys and literature review, a final matrix of prioritized species emerged and a 20-year agenda of implementation is proposed. This might be the first time in Colombia where suitable species and products that accomplish sustainability criteria are prioritized based on the community's traditional knowledge and the scientific evidence. Based on this new evidence, decision-makers and environmental government institutions are encouraged to use this information to focus their development agendas and research projects.